Single neuron transcriptomics identify SRSF/SR protein B52 as a regulator of axon growth and Choline acetyltransferase splicing. - Liu, B.; Bossing, T. (Scientific reports, 2016)
We removed single identified neurons from living Drosophila embryos to gain insight into the transcriptional control of developing neuronal networks. The microarray analysis of the transcriptome of two sibling neurons revealed seven differentially expressed transcripts between both neurons (threshold: log21.4). One transcript encodes the RNA splicing factor B52. Loss of B52 increases growth of axon branches. B52 function is also required for Choline acetyltransferase (ChAT?) splicing. At the end of embryogenesis, loss of B52 function impedes splicing of ChAT, reduces acetylcholine synthesis, and extends the period of uncoordinated muscle twitches during larval hatching. ChAT regulation by SRSF proteins may be a conserved feature since changes in SRSF5 expression and increased acetylcholine levels in brains of bipolar disease patients have been reported recently.